THE EFFECT OF PLAYING METHOD TOWARD BASIC SKILLS OF STUDENTS’ PLAYING FOOTBALL - Novri Gazali; Romi Cendra (Universitas Negeri Medan, 2019)
The research aimed to reveal the effects of playing methods for basic skills in football. The type of this research was quasy experiment. Population in this research was 32 students of SMPN 3 Singingi Hilir Kuansing Regency Riau Province, and the sample in this research after using purposive sampling was 20 students. Research instrument used in this research was football skills test David Lee which was the development from David Lee created by Subagyo Irianto. Data was analyzed by statistics of normality-test and t-test. Data analysis results showed that there was a significant effect in playing method for basic technique skills in football, which was from average 26.20 in pre-test to 27.84 in post-test, mean difference was 1.64, with thit = 3.17> ttab = 1.729. The method of playing gave a significant influence on the basic skills of playing football of SMP Negeri 3 Singingi Hilir students in Kuansing Regency, Riau Province.